2021
DOI: 10.1021/acs.inorgchem.1c01004
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the π-Accepting Properties of Borate-, Aluminate-, and Gallate-Functionalized N-Heterocyclic Carbenes by 77Se NMR Spectroscopy

Abstract: Anionic N-heterocyclic carbenes with weakly coordinating borate, aluminate, and gallate moieties of the type [(F 5 C 6 ) 3 E-NHC] − (E = B, Al, Ga) were isolated as lithium salts by the lithiation of 1,3-bis(2,4,6-trimethylphenyl)imidazolin-2-ylidene (IMes) or 1,3-bis(2,6-diisopropylphenyl)imidazolin-2-ylidene (IDipp) followed by the addition of E(C 6 F 5 ) 3 (E = B, Al, Ga). Treatment with elemental selenium afforded the lithium salts of the corresponding anionic selenourea derivatives [{(F 5 C 6 ) 3 E-NHC}Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…All yields were calculated based on the WCA-IDipp containing substrate. [Rh(COD)Cl] 2 , [34] [Ir(COD)Cl] 2 , [35] [(η 5 -C 5 Me 5 )RhCl 2 ] 2 , [36] [(η 5 -C 5 Me 5 )IrCl 2 ] 2 , [37] [{(WCA-IDipp)S}Li(toluene)] [17] and [{(WCA-IDipp)Se} Li(toluene)] [18] were prepared according to literature procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All yields were calculated based on the WCA-IDipp containing substrate. [Rh(COD)Cl] 2 , [34] [Ir(COD)Cl] 2 , [35] [(η 5 -C 5 Me 5 )RhCl 2 ] 2 , [36] [(η 5 -C 5 Me 5 )IrCl 2 ] 2 , [37] [{(WCA-IDipp)S}Li(toluene)] [17] and [{(WCA-IDipp)Se} Li(toluene)] [18] were prepared according to literature procedures.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Furthermore, the 77 Se NMR spectra of the selenides [{(WCA-NHC)Se}Li(toluene)] were studied to determine the πaccepting properties of the WCA-NHCs, revealing that the counter cation does not exert any significant influence, if it is fully separated from the selenium atom by solvation, for example, in THF-d 8 . [18] In this context, we envisaged that the lithium salts [{(WCA-IDipp)E}Li(toluene)] (1: E = S; 2: E = Se) or, similarly to I, the trimethylsilyl derivatives (WCA-IDipp)ESiMe 3 (3: E = S; 4: E = Se) might serve as suitable reagents for the transfer of the anionic (WCA-IDipp)E À ligand (III, Figure 1). The resulting metal complexes of the type [{(WCA-IDipp)E}ML n ] (E = S, Se) will have an identical total charge as the corresponding NHC-phosphinidenide complexes [{(IDipp)P}ML n ] and therefore allow the comparison of the phosphorus-metal and chalcogen-metal bonds, while preserving the overall structural and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…All solvents were stored over molecular sieves (4 Å) in argon atmosphere prior to use. [{(WCA‐IDipp)S}Li(toluene)], [20] [{(WCA‐IDipp)Se}Li(toluene)], [17] (WCA‐IDipp)SSiMe 3 [21] and (WCA‐IDipp)SeSiMe 3 [21] were prepared according to literature procedures. For crystallographic details, see the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting anionic N‐heterocyclic carbenes (WCA‐NHC) [13] were introduced as ancillary ligands for transition metal complexes and homogeneous catalysts [14–16] . Concurrently, the main group element chemistry with the WCA‐NHC ligands witnessed a similar extensive development [17–19] . The isolation of anionic chalcogen complexes VI bearing the WCA‐IDipp ligand is particularly important in the context of this work, and it has been demonstrated that these species can be converted into WCA‐IDipp‐stabilized disulfide and diselenide compounds VII under oxidative conditions [20] .…”
Section: Introductionmentioning
confidence: 99%
“…[12] Related anionic analogues of NHCs in which the borate unit is attached to the heterocycle via a methylene (CH 2 ) spacer were also used in transition metal chemistry. [13] Lately, the lithium salts 1 were employed for the preparation of WCA-NHC complexes of the heavier p-block elements, covering groups 13, [14] 15, [15] 16, [16] and 17. [17] In search for alternative transmetalation reagents, sodium and potassium salts of WCA-NHCs were recently introduced, however, their synthesis through deprotonation of IDipp with It should be noted that formal charges are shown here to illustrate the anionic nature of the N-heterocyclic carbene ligands; in the following, however, formal charges will be omitted to avoid the assignment of awkward charges in transition metal complexes.…”
Section: Introductionmentioning
confidence: 99%